PENGEMBANGAN MODUL AJAR KONSEP DASAR IPA (BIOLOGI) UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS MAHASISWA - Permatasari, Faudina (LENSA (Lentera Sains): Jurnal Pendidikan IPA, 2025)
PGSD students come from various majors when they are in high school, so that those who were not science majors have difficulty following basic science concepts courses. The purpose of this study was to develop a module based on process skills in biological material for basic science courses and to determine student perceptions of the modules developed. This type of research is development research with the 4D development model by Thiagarajan. The subjects of this study were Jambi University Physics Education students. The instruments used were material expert validation questionnaires, media experts and student perception questionnaires. The results of validation of the material are 82.5% with a very good category, media experts are 86% with a very good category. Perception data obtained 82.94% with a very good category with a reliability of 0.892 these results indicate that the questionnaire used has a very high reliability. Based on these results, it can be concluded that the developed module is feasible to use as learning media in the implementation of learning Basic Science Concepts course. Keywords: skills, process, science, basic